Contribuições de uma Unidade de Aprendizagem sobre estatística com o recurso da planilha - Cunha, Márcia Loureiro da (2012)
This paper aims to analyze the contributions of a Learning Unit for the application of statistical concepts using the spreadsheet. The field research was conducted with students in their sixth year of elementary school in a school hall on the outskirts of the metropolitan area of Porto Alegre, Rio Grande do Sul. The analysis was the identification of students' prior knowledge of statistical concepts and computer use. From the responses received to a questionnaire given initial investigation is the preparation and organization of the Learning Unit. Based on observations of teacher and researcher in the analysis of the materials produced by students, we investigate how is the understanding of statistical concepts through a Learning Unit with the use of spreadsheet features. The results showed a trend in the level of statistical literacy of participating students, it also noted positive changes in behavioral terms and their relationships in the group.